Settlement of Problem Loans with Cessie Guarantee at Bank Jateng - Delvachio, Muhammad Rayhan Abrar; Dona Budi Kharisma (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2024)
This research aims to determine the mechanism for resolving problem loans by binding collateral in the form of cession at Bank Jateng, as well as a guarantee binding scheme in the form of cession in the government project credit agreement at Bank Jateng. This research is only limited to examining the implementation of projects funded by the government which are tied to guarantees cession. This research uses empirical legal research methods, and is descriptive in nature. The types of data used include primary data and secondary data. The data collection techniques used in collecting data in this research were interviews and document study in the form of statutory regulations, books, documents relevant to the research. The data analysis technique uses qualitative data analysis. The presence of the Covid-19 pandemic as a global outbreak has had an impact on economic activity. This is characterized by the stagnation of various business sectors, especially in terms of implementing government project credit. Of course, this condition causes disruption to banking operational activities, especially in terms of the risk of problematic credit with cessie collateral. Instability and the high number of non-performing loans during the pandemic have created major problems. Responding to these conditions, this article provides an analysis regarding the resolution of problem loans in terms of the concept of implementing government projects tied to a cessie guarantee scheme and referring to OJK regulations regarding restructuring. Settlement of problem loans can be resolved through the restructuring implementation scheme and the concession itself. The collateral separation binding scheme in the government project credit agreement itself can be carried out in 3 (three) ways, namely through (1) prior notification, approval and acknowledgment of the full transfer of receivables to the debtor; (2) hand over the agreement in the form of an authentic deed, and (3) hand over the guarantee directly to the Bank.